An Elderly Patient With Crouzon Syndrome Treated With Monobloc Distraction. Issue 8 (5th November 2022) - Nakao, Ko; Sakamoto, Yoshiaki; Miwa, Tomoru; Wakabayashi, Kenichiro; Ishii, Takenobu; Kishi, Kazuo
Abstract : Monobloc advancement by distraction osteogenesis is the treatment of choice in patients with syndromic craniosynostosis. This procedure is usually performed at 18 to 24 months/5 to 10 years of age. Herein, we present the case of a male patient with Crouzon syndrome who underwent monobloc advancement at the age of 62 years. Although the patient lived a normal life (employed, married, and being a father of a daughter), he visited our hospital for surgical improvement in facial esthetics. The patient underwent monobloc advancement by distraction osteogenesis. He was satisfied with the postoperative esthetic improvement and did not experience any major complications. This case highlights the fact that patients with syndromic craniosynostosis desire esthetic improvement and suggests that multidisciplinary treatment involving both the neuro and plastic surgeons is important in such cases.